Efektivitas Latihan Plyometric Depth Jump Dan Plyometric Box Jump Terhadap Peningkatan Vertical Jump Pada Atlet Voli Putri Di Bintang Physio Bandung - Dayanara Elsa Amedika; Fransisca Xaveria Hargiani; Nurul Halimah; Angria Pradita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Sports is an activity that is widely carried out by the community and its existence for now is no longer considered something that can be underestimated, because related things have played a variety of people's lives, Physiotherapy is also one of the health professions that has a close relationship with sports that aims to help restore and maximize the function, movement, strength of the body as a whole in sports actors, especially athletes.Methods: The study design was carried out together with quantitative studies, together using the Two Group Pretest-Posttest study design to determine the effectiveness of plyometric depth jump and plyometric box jump exercises in women's volleyball athletes. Results: The effectiveness of giving plyometric depth jump and plyometric box jump exercises between 2 groups of women's volleyball athletes at the Bintang Physio Clinic Bandung, the results of the vertical jump test pre Plyometric box jump group were higher than the Plyometric depth jump group and statistically it was stated that there was a significant difference (p = 0.000).